Hepatitis E virus in a young pregnant woman - Fidel Alejandro Almeida Lobaina; Yorgan Gómez Neira; Carmen Elsa Hechavarria Kindelán (Centro Provincial de Información de Ciencias Médicas, 2018)
The case report of a 20 years nonparous pregnant woman with history of intermittent, asymptomatic asthma is presented, who was admitted with an icteric syndrome in "Mariana Grajales Coello" Gynecoobstetric Hospital of Santiago de Cuba. After carrying out him the pertinent studies it was concluded that she presented a complicated hepatitis E, which required intensive cares; with the opportune diagnosis and the effective treatment her survival could be guaranteed.